Association of parental feeding styles and the nutritional status of children ages 2 to 5 years in Jember, East Java, Indonesia - Marchianti, Ancah Caesarina Novi; Rachmawati, Dwita Aryadina; Astuti, Ida Srisurani Wiji; Raharjo, Angga Mardro; Kusuma, Irawan Fajar; Sudarmanto, Yohanes; Hakiim, Arsyzilma; Nurmaida, Eny (Universitas Udayana, 2024)
Background and purpose: There is a great deal of mythical erroneous information regarding children's nutrition that can affect styles of parental feeding. If it is left uncontrolled, it may influence the nutritional status that led to malnutrition. The purpose of this study is to determine association between styles of parental feeding and nutritional status of children ages of 2 to 5 years old. Methods: This was a cross-sectional study, conducted in November-December 2023 in Jember, East Java, Indonesia. Samples were 244 mothers who were selected purposively and satisfied the inclusion and exclusion criteria. Data was collected with interview which include parents’ and children’s characteristics, the feeding practices using a validated structured questionnaire (FPSQ-28), and children nutritional status. Descriptive analysis followed by correlation analysis were performed. Results: Most parents earn more than IDR 2,000,000 and work as self-employed, whereas more than half of the respondents, both fathers and mothers, had at least a high school education, and the majority of height in both were 150-170 cm with normal body mass index. There is a weak positive association between the styles of parental feeding with the body weight for age (r=0.183; p=0.040) while no significant association with body weight for height (r=0.08; p=0.216). Conclusion: Styles of parental feeding affected children's feeding and nutritional status, particularly when it comes to chronic conditions and in order to maintain children's nutrition or balanced nutrition, it is necessary to conduct education and evaluation of parental feeding styles.